MOLECULAR CHARACTERIZATION OF Colletotrichum SPP. ISOLATES ASSOCIATED WITH POST-BLOOM FRUIT DROP - Da Silveira, Amanda Leticia; Stracieri, Juliana [UNESP]; Pereira, Fernanda Dias [UNESP]; De Souza, Andressa [UNESP]; De Goes, Antonio [UNESP] (Soc Brasileira Fruticultura, 2016)
Postbloom fruit drop of citrus (PFD) is a serious disease of this crop, accounting for high yield losses. Usually, this disease shows to be limiting when there are prolonged rainy periods during plant-flowering or when there is intense leaf wetness. Two Colletotrichum species are associated with the disease: C. actitatum and C. gloeosporioides. However, recently, it has been found that, even under not so favorable conditions, the disease has occurred with sonic frequency; one suspects the involvement of other Colletotrichum species or new adaptation conditions of the described species. This study aimed to determine whether there is another Colletotrichum species associated with PFD and the viability of using molecular markers ISSR for taxonomic characterization of Colletotrichum spp. isolates associated with PFD symptoms in flowers, as well as of leaf tissues and asymptomatic citrus fruits. For this purpose, we used a combination of specific primers, taking into account the ITS region and ISSR molecular markers. ISSR markers have proven to be effective for taxonomic characterization of the Colletotrichum isolates analyzed. The population assessed consisted only of C. acutatum and C. gloeosporioides, discarding the involvement of an additional species. We found high genetic diversity among the isolates analyzed, which is also shown as converging to the phenotypic differences observed under field conditions. However, no relation was found regarding the origin and associated Colletotrichum spp. species. In an unprecedented way, although asymptomatically, we detected the presence of a C. actilalum isolate associated with citrus fruits.
Keywords: Citrus SitlenSiS; ISSR markers; ITS region